Al-‘Afālu al-Kalāmiyatu al-Taujihiyyatu fī al-Rusūmi al-Mutaharrikati “al-Riḥlatu” (Dirāsatu tahlīliyatu tadāwuliyatu) - Sukmawati, Amalia; Yusuf, Mohammad; Khasanah, Mushokhikhul (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
Directive speech act is an utterance performed by a speaker which has the function of making the other person act as what is said. One of the directive speech acts was found in the animation